Cloning, distribution, and effects of growth regulation of MC3R and MC4R in red crucian carp (Carassius auratus red var.) - Huang, Lu; Deng, Xin; Yang, Xiangqiong; Tang, Zhong; Fan, Siyu; Zhou, Zhifeng; Tao, Min; Liu, Shaojun (Frontiers in Endocrinology, 2024)
Melanocortin-3 and -4 receptors (MC3R and MC4R), G protein-coupled receptors, play vital roles in the regulation of energy homeostasis. To understand the functions of MC3R and MC4R in the energy homeostasis of red crucian carp (Carassius auratus red var., RCC), we cloned the mc3r and mc4r, analyzed the tissue expression and localization of the genes, and investigated the effects of knockout of mc3r (mc3r +/-) and mc4r (mc4r +/-) in RCC. The full-length cDNAs of RCC mc3r and mc4r were 1459 bp and 1894 bp, respectively. qRT-PCR indicated that mc3r and mc4r were profusely expressed in the brain, but lower expressed in the periphery tissues.ISH revealed that mc3r and mc4r located in NPP, NPO, NAPv, NSC, NAT, NRL, NLTl, and NLTp of the brain, suggesting mc3r and mc4r might regulate many physiological and behavioral aspects in RCC. To further verify the roles of mc3r and mc4r in energy homeostasis, the mc3r +/-and mc4r +/-fish were obtained by CRISPR/Cas9 system. The average body weights, total lengths, body depths and food intake of mc4r +/-fish were significantly higher than mc3r +/-and the normal wild type (WT) fish, but there was no difference between the mc3r +/-and WT fish, indicating the RCC phenotype and food intake mainly were influenced by mc4r but not mc3r.Interestingly, mc4r +/-fish displayed more visceral fat mass than mc3r +/-and WT fish, and mc3r +/-fish also exhibited slightly more visceral fat mass compared to WT.RNA-seq of the liver and muscle revealed that a large number of differentially expressed genes (DEGs) differed in WT vs. mc3r +/-, WT vs. mc4r +/-, and mc3r +/-vs. mc4r +/-, mainly related to lipid, glucose, and energy metabolism. The KEGG enrichment analysis revealed that DEGs mainly enriched in the following pathways, such as steroid biosynthesis, fatty acid metabolism, fatty acid biosynthesis, glycolysis/gluconeogenesis, wnt signaling pathway, PPAR signaling pathway, MAPK signaling pathway, and others, thereby affecting the lipid accumulation and growth. In conclusion, these results will assist in further investigation of the molecular mechanisms that MC3R and MC4R were involved in the regulation of energy homeostasis in fish.